The road to Bukittinggi: Aziz Ishak’s rendition in his Mencari Bako - Mohd Noor Merican, Ahmad Murad (Melaka Hari Ini Sdn. Bhd., 2021)
In his Mencari Bako (Searching for Roots), published in 1983, a memoir of his journey in search of origins and ancestors, Abdul Aziz Ishak tells us the story about his larger family, his encounters with fellow Minangkabaus and community, and the history of the Malays. His ancestors traversed their way to what is now North Sumatra from Pagaruyung, and Payakumbuh. And in the ways of the merantau, finally took residence in what is now Minden and Batu Uban, Pulau Pinang. Aziz (1913 – 1999) former colonial civil servant, journalist and politician was a Minister under Tunku Abdul Rahman’s cabinet.